Theoretical investigation of flow past bluff-bodies - Wong, Anthony Tsz Him. (2009)
In this final year project, the author will be performing a series of analysis on the uniform potential flow past multiple circular cylinders. A bluff-body is one which has a comparable dimension along the x and y axes. For an ideal flow past a symmetrical bluff-body such as a circular cylinder, the streamlines form a symmetric pattern. The effect of viscous flow which will create boundary layers and flow separation will not be discussed.